Shock wave and modelling study of the dissociation kinetics of C₂F₅I - Cobos, Carlos Jorge (2021)
The thermal dissociation of C₂F₅I was studied in shock waves monitoring UV absorption signals from the reactant C₂F₅I and later formed reaction products such as CF, CF₂, and C₂F₄. Temperatures of 950–1500 K, bath gas concentrations of [Ar] = 3 × 10⁻⁵ –2 × 10⁻⁴ mol cm⁻³, and reactant concentrations of 100–500 ppm C₂F₅I in Ar were employed. Absorption-time profiles were recorded at selected wavelengths in the range 200–280 nm. It was found that the dissociation of C₂F₅I → C₂F₅ + I was followed by the dissociation C₂F₅ → CF₂ + CF₃, before the dimerization reactions 2CF₂ → C₂F₄ and 2CF₃ → C₂F₆ and a reaction CF₂ + CF₃ → CF + CF₄ set in. The combination of iodine atoms with C₂F₅ and CF₃ had also to be considered. The rate constant of the primary dissociation of C₂F₅I was analyzed in the framework of statistical unimolecular rate theory accompanied by a quantum-chemical characterization of molecular parameters. Rates of secondary reactions were modelled as well. Experimental rate constants for the dissociations of C₂F₅I and C₂F₅ agreed well with the modelling results. The comparably slow dimerization 2CF₂ → C₂F₄ could be followed both by monitoring reactant CF₂ and product C₂F₄ absorption signals, while CF₃ dimerization was too fast to be detected. A competition between the dimerization reactions of CF₂ and CF₃, the recombination of CF₂ and CF₃ forming C₂F₅, and CF-forming processes like CF₂ + CF₃ → CF + CF₄ finally was discussed.